The combination of murashige and skoog (MS) media and activated charcoal on the growth of the Vanda helvola orchid plant in vitro - Ata Rofita Wasiati; Ika Afifah Nugraheni; Yuli Setiawati (International Journal of Health Science and Technology, 2021)
Orchids of the Vanda helvola genus are extensively grown as ornamental plants. The method of propagation of plant seeds in tissue culture is an alternative that may be employed in the provision of a short period. Murashige and Skoog (MS) media and activated charcoal can optimize orchid cultivation utilizing tissue culture techniques. One of the keys to success in tissue culture is the application of natural types of growing regulatory substances (ZPT) at the proper concentration, which can lower the cost of orchid tissue culture.The objective of this study was to see how a combination of Murashige and Skoog (MS) media and activated charcoal influenced the Vanda helvola orchid subculture in vitro. The researchers employed a Complete Randomized Design (RAL) with four treatments and three repeats: negative control (K), ¼ MS (K1), ½ MS (K2), and 100% MS (K3) (K3). The observed parameters include the percentage of live explant, number of roots, and height of orchid plants.   The results showed that the explant had a 100% life percentage of over 21 HST and had no noticeable influence on the number of roots and the plant's height.